Bahasa Inggris THE IMPACT OF SELF-SATISFACTION AND DISTRACTION ON KALLA INTI KARSA EMPLOYEES PERFORMANCE WITH FOMO MODERATION - Muhammad Fajar Nur; Suhartini, Eka; Indriyani, Eka; Effendi, Ahmad; Rusnawati (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
Social media can hinder employee performance in companies, as different levels of self-satisfaction and distractions affect productivity. This research aims to determine the effect of self-satisfaction and work distractions on employee performance, with fear of missing out (FOMO) as a moderator. The study uses primary data, with non-probability sampling and a sample size of 135, based on a formula by Isaac & Michael. It employs quantitative research methods, focusing on Kalla Inti Karsa employees with a minimum of one year of experience, up to middle manager level. Data analysis is conducted using SEM and SmartPLS software. Results indicate that self-satisfaction significantly and positively affects employee performance. Distraction at work does not have a significant negative effect on performance. FOMO significantly and positively moderates the relationship between self-satisfaction and performance but does not significantly moderate the impact of distraction at work on performance.